Design and analysis of four-bar linkage transplanting mechanism incorporating compliance linkage - Ngamvilaikorn, Tawee; Chooprasird, Kummun (Agriculture and Natural Resources, 2026)
Importance of the work: A novel transplanting mechanism was developed and tested, combining a four-bar linkage with a compliance linkage, enabling continuously adjustable planting distances without requiring mechanical reconfiguration. Objectives: To design and test a four-bar linkage transplanting mechanism incorporating a compliance linkage for precision agriculture. Materials and Methods: A transplanting mechanism was developed and mounted on a mobile crane. Kinematic modeling, kinetic analysis and spring-stiffness calculations were conducted to ensure a zero-speed planting condition (λ ≈ 1). Field tests were performed using five vegetable types. Results: The mechanism achieved high precision in planting: cabbage (mean spacing = 31.5 cm, coefficient of variation, CV = 4.56%), lettuce (25.8 cm, CV = 4.31%), green onion (10.2 cm, CV = 3.65%), sweet chard (20.7 cm, CV = 4.12%), and Chinese celery (15.3 cm, CV = 3.89%). The qualified transplanting rate exceeded 95% for all crops. The system achieved a planting rate of 828 seedlings/hr/row—nearly three times faster than manual transplanting. Main finding: This new mechanism enables infinitely variable planting distances, allowing it to accommodate nearly any vegetable type—an adaptability that conventional transplanting systems lack.